2016
DOI: 10.1002/2016wr019061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mercury cycling and hypolimnetic oxygenation in mercury-impacted seasonally stratified reservoirs in the Guadalupe River watershed, California

Abstract: Surface water reservoirs trap inorganic mercury delivered from their watersheds, create conditions that convert inorganic mercury to highly toxic methylmercury (MeHg), and host sportfish in which MeHg bioaccumulates. The Santa Clara Valley Water District (District) actively manages and monitors four mercury‐impaired reservoirs that help to serve communities in South San Francisco Bay, California. The Guadalupe River watershed, which contains three of those reservoirs, also includes the New Almaden mercury‐mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…In addition, eutrophication can alter organic carbon loads to surface waters, resulting in mixed effects that can increase or decrease MeHg levels in surface waters, as noted above. Managed alterations such as additions of nitrate or hypolimnetic oxygenation in the field have been attempted with some success to change redox conditions and decrease MeHg concentrations in water, but these manipulations do not always result in reductions of MeHg in biota (Matthews et al 2013 ; Austin et al 2016 ; Beutel et al 2016 ; McCord et al 2016 ).…”
Section: Altered Surface Loadingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, eutrophication can alter organic carbon loads to surface waters, resulting in mixed effects that can increase or decrease MeHg levels in surface waters, as noted above. Managed alterations such as additions of nitrate or hypolimnetic oxygenation in the field have been attempted with some success to change redox conditions and decrease MeHg concentrations in water, but these manipulations do not always result in reductions of MeHg in biota (Matthews et al 2013 ; Austin et al 2016 ; Beutel et al 2016 ; McCord et al 2016 ).…”
Section: Altered Surface Loadingsmentioning
confidence: 99%
“…Though not unique to just reservoirs, management strategies in waterbodies aimed at altering redox conditions through oxygen or nitrate addition can also be utilized to reduce MeHg production (Matthews et al 2013 ; McCord et al 2016 ). Other management actions aimed at decreasing MeHg production can include reducing the size and/or development of an anoxic hypolimnion using lake mixers or selective water withdrawals (Rask et al 2010 ; Perron et al 2014 ; Zouabi-Aloui et al 2015 ).…”
Section: Reservoir Creationmentioning
confidence: 99%
“…Spatial and temporal patterns of MeHg production within a reservoir will be influenced by the inflow of IHg, labile carbon, availability of terminal electron acceptors, and the timing and duration of thermal and redox stratification, among other variables. 11,12 In contrast, the fate of hypolimnetic MeHg released from a reservoir will be controlled by the timing and duration of thermal destratification. 8,13 Previous studies have reported seasonally elevated MeHg concentrations at reservoir outflow versus inflow locations, 1,8,14,15 suggesting that MeHg produced within a reservoir can be exported downstream.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, the relatively high COD Mn in summer also indicated that the DO consumption was higher than in other seasons. DO in summer had a corresponding decrease trend in water in low water level operation [37].…”
Section: Dissolved Oxygen (Do)mentioning
confidence: 93%